Ensure security in supply chain with blockchain technology - Tarannum, Fairuz; Nafiz, Nazibun; Khanam, Sumaya; Tabassum, Wasy; Kamor, Rudaba Adnin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.